2021
DOI: 10.1200/jco.2021.39.15_suppl.1039
|View full text |Cite
|
Sign up to set email alerts
|

Safety of trastuzumab emtansine (T-DM1) in patients (pts) with HER2-positive locally advanced or metastatic breast cancer (mBC): Final results from KAMILLA Cohorts 1 (global) and 2 (Asia).

Abstract: 1039 Background: KAMILLA is an open-label, single-arm, phase 3b safety study of T-DM1 in pts with HER2-positive advanced BC (NCT01702571). The treated (safety) population of KAMILLA comprises 2 cohorts: a larger global Cohort 1 (n=2002) and a smaller Asia Cohort 2 (n=181 [China, n=154; Thailand, n=15; Indonesia, n=12]). Here we report results from Cohort 2 in the context of those previously reported for Cohort 1. Methods: Pts had HER2-positive, locally advanced or mBC with progression after chemotherapy and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…The incidence of thrombocytopenia AEs in Chinese patients in ELAINA (the current study), is higher than that reported in studies with global populations, including EMILIA ( 18 , 19 ). This is consistent with prior studies demonstrating an increased risk of thrombocytopenia in Asian patients vs. non-Asian patients ( 20 - 22 , 30 ). In a pooled analysis of six studies of T-DM1 in patients with HER2-positive mBC, Asian patients demonstrated a higher incidence of grade ≥3 decreased platelet count than non-Asian patients (44.4% vs. 10.6%) ( 20 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The incidence of thrombocytopenia AEs in Chinese patients in ELAINA (the current study), is higher than that reported in studies with global populations, including EMILIA ( 18 , 19 ). This is consistent with prior studies demonstrating an increased risk of thrombocytopenia in Asian patients vs. non-Asian patients ( 20 - 22 , 30 ). In a pooled analysis of six studies of T-DM1 in patients with HER2-positive mBC, Asian patients demonstrated a higher incidence of grade ≥3 decreased platelet count than non-Asian patients (44.4% vs. 10.6%) ( 20 ).…”
Section: Discussionsupporting
confidence: 93%
“…A similar difference was observed in Asian patients (43.8%) vs. the global population of EMILIA (13.9%) (21). The results from ELAINA are also consistent with the international, single-arm, phase IIIb KAMILLA trial of T-DM1 in HER2-positive mBC, in which grade ≥3 thrombocytopenia occurred in 44.7% and 3.7% of Asian and non-Asian patients, respectively (22). In these studies (20)(21)(22), thrombocytopenia in Asian patients was not associated with an increased incidence of clinically significant hemorrhage and could generally be managed with the T-DM1 dose adjustments recommended for the global population (29).…”
Section: Pkssupporting
confidence: 79%
See 2 more Smart Citations